Minimal inhibitory concentrations of modern topical antimicrobials - T. N. Vorontsova; V. Y. Popov; V. J. Shaporova (Oftalʹmologiâ)
Aim. To measure minimal inhibitory concentration (MIC) values for modern topical antimicrobials against common ocular pathogens.Methods.Antimicrobials most commonly used in ophthalmology (fluoroquinolones and aminoglycosides) are dose-dependent drugs, i.e., the rate of microbial death increases in direct proportion to their concentrations. To determine MICs, we applied Hi Comb MIC Test (E-test). 105 patients aged 2 months through 7 years which were diagnosed with various inflammatory disorders of anterior segment were  xamined. MIC values for most commonly used antimicrobials, i.e., ciprofloxacin / Cipromed (Sentiss Pharma, Gurgaon, India), ofloxacin / Floxal (Baush & Lomb, Rochester, New-York), levofloxacin / Signicef (Sentiss Pharma, Gurgaon, India), moxifloxacin / Vigamox (Alcon, Fort Worth, Texas), gatifloxacin / Zymar (Allergan, Irvine, California), and tobramycin / Tobrex (Alcon, Fort Worth, Texas), were measured.Results. The analysis revealed that the most effective antibacterial drug against microbial isolates in children (i.e., Staphylococci spp.) was levofloxacin. MIC for this agent against Streptococci spp. and Gram-negative microbes was low as well. Moxifloxacin is preferred for the treatment of ocular inflammation provoked by Streptococci spp. as MIC of this antimicrobial against Streptococci spp. was the lowest. MIC of ciprofloxacin against Gram-negative flora was the lowest. These data demonstrate generally recognized high efficacy of this drug. MIC value for tobramycin against all bacterial isolates was the highest.